Answer:
4.5
Step-by-step explanation:
Hello, please consider the following.
First of all, let's assume that A is different from 0.
[tex]x^2+8x+4\\\\\text{It means that the sum of the zeroes is -8 and the product is 4}\\\\Ax^2+Bx+1=A(x^2+\dfrac{B}{A}x+\dfrac{1}{A})\\\\\text{So the sum of the zeroes is } -\dfrac{B}{A} \text{ and the product is }\dfrac{1}{A}\\\\\text{It comes.}\\\\-\dfrac{B}{A}=-8 <=> \dfrac{B}{A}=8\\\\\dfrac{1}{A}=4[/tex]
So,
[tex]A=\dfrac{1}{4}\\\\B=\dfrac{8}{4}=2\\\\A+B=\dfrac{1+8}{2}=\dfrac{9}{2}=4.5[/tex]
Thank you.